Thyroid cancer patients satisfaction at the management outcome: an analysis of the results of a nationwide survey in 485 subjects - Díez, Juan J.; Galofré, Juan C. (BMC health services research, 2021)
We aimed to measure satisfaction of patients with thyroid cancer concerning different aspects of healthcare. We developed a web-based survey. Questions focused on patient satisfaction with specialists, the health centers and departments, and the information received about their disease. Level of satisfaction was quantified using a scale of 1 to 5. Values ≥4 were considered a high degree of satisfaction. Four hundred eighty-five patients (aged 43.4 ± 9.9 yrs., 88% females) completed the survey. A high overall satisfaction with the specialists was reported by 52.5% of patients. The most highly valued specialists were surgeons, oncologists, and endocrinologists. 56.5% of respondents reported a high overall satisfaction with the health centers and departments. Lastly, the proportion of patients who were highly satisfied with the information received was only 42.5%. The presence of complications was indirectly related with satisfaction with specialists and information. Satisfaction with health centers and services was directly related with the level of education and inversely related to the time of evolution of the disease. Our results show a high degree of overall satisfaction of thyroid cancer patients. However, satisfaction can be improved in some areas, such with regards to the information provided to patients.